2020
DOI: 10.1002/hep4.1495
|View full text |Cite
|
Sign up to set email alerts
|

Loss of c‐Jun N‐terminal Kinase 1 and 2 Function in Liver Epithelial Cells Triggers Biliary Hyperproliferation Resembling Cholangiocarcinoma

Abstract: Targeted inhibition of the c-Jun N-terminal kinases ( JNKs) has shown therapeutic potential in intrahepatic cholangiocarcinoma (CCA)-related tumorigenesis. However, the cell-type-specific role and mechanisms triggered by JNK in liver parenchymal cells during CCA remain largely unknown. Here, we aimed to investigate the relevance of JNK1 and JNK2 function in hepatocytes in two different models of experimental carcinogenesis, the dethylnitrosamine (DEN) model and in nuclear factor kappa B essential modulator (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
(62 reference statements)
2
22
0
Order By: Relevance
“…Previous studies have established that hepatic JNK deficiency can suppress cholangiocyte proliferation and oncogenic transformation in a p53/Kras-induced model of cholangiosarcoma (35) and promotes cholangiocarcinoma in dethylnitrosamine and NEMO deficiency models of liver cancer (36). The results of the present study demonstrate that hepatic JNK deficiency is sufficient for the development of cholangiocyte malignancy (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have established that hepatic JNK deficiency can suppress cholangiocyte proliferation and oncogenic transformation in a p53/Kras-induced model of cholangiosarcoma (35) and promotes cholangiocarcinoma in dethylnitrosamine and NEMO deficiency models of liver cancer (36). The results of the present study demonstrate that hepatic JNK deficiency is sufficient for the development of cholangiocyte malignancy (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…( 20 ) However, when these mice are treated with a carcinogen (i.e., DEN), the process can be accelerated, and histological and molecular features consistent with human iCCA are observable much earlier. ( 19 ) Therefore, we treated 2‐week‐old Jnk Δhepa mice with a single dose of DEN, and at 8 weeks started to receive CCl 4 twice per week until 22 weeks of age ( Jnk Δhepa + DEN + CCl 4 mice; Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Besides finding reduced growth of xenografted CCA cells, and a strong growth inhibitory effect in a human CCA PDX mouse model, we observed a remarkable effect in a recently developed mouse model reproducing early stages of cholangiocarcinogenesis. Mice with hepatocellular deletion of Jnk1/2 develop hepatic lesions morphologically and molecularly resembling human CCA progression when subjected to liver injury, or spontaneously at later time points (19,20). Expression of the CM272 targets G9a and DNMT1 was readily detected in cyst-like structures compatible with cholangioma or malignant CCA compared with normal cholangiocytes.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated a requirement of Jnk for hepatic cyst formation in models of mitochondrial redox stress-induced cholangiocarcinoma [73]. However, this role of JNK to promote cystogenesis appears to be dependent on physiological context because Jnk deletion alone was sufficient to cause hepatic cyst formation in another study of aged mice [74][75][76]. JNK signaling may have tissue-specific roles in ADPKD that will be important to evaluate for therapeutic development.…”
Section: Discussionmentioning
confidence: 96%